Investigation the efficacy of intra-articular prolotherapy with erythropoietin and dextrose and intra-articular pulsed radiofrequency on pain level reduction and range of motion improvement in primary osteoarthritis of knee - Rahimzadeh, Poupak (J Res Med Sci, 2014)
BACKGROUND: Osteoarthritis is one of the most common diseases and the knee is the most commonly affected joint. Intra-articular prolotherapy is being utilized in acute and chronic pain management setting. This study was designed to compare the efficacy of three methods of intra-articular knee joint therapies with erythropoietin, dextrose, and pulsed radiofrequency. MATERIALS AND METHODS: After approval by the Ethics Committee and explaining the therapeutic method to volunteers, 70 patients who were suffering from primary knee osteoarthrosis went through one of the treatment methods (erythropoietin, dextrose, and pulsed radiofrequency). The study was double-blind randomized clinical trial performed from December 2012 to July 2013. Patients’ pain level was assessed through the visual analog pain scale (VAS), and range of motion (ROM) was measured by goniometric method. Furthermore, patients’ satisfaction was assessed before and after different treatment methods in weeks 2, 4, and 12. For analysis, Chi-square, one-way ANOVA, and repeated measured ANOVA were utilized. RESULTS: The demographic results among the three groups did not indicate any statistical difference. The mean VAS in erythropoietin group in the 2(nd), 4(th), and 12(th) weeks was 3.15 ± 1.08, 3.15 ± 1.08, and 3.5 ± 1.23, respectively (P ≤ 0.005). Knee joint ROM in the erythropoietin group in the 2(nd), 4(th), and 12(th) weeks was 124 ± 1.50, 124 ± 1.4, and 123 ± 1.53 respectively (P ≤ 0.005). Satisfaction score in the 12(th) week in erythropoietin group was extremely satisfied 15%, satisfied 55%, and moderately satisfied 30%, (P = 0.005). No specific side-effects were observed. CONCLUSION: Intra-articular prolotherapy with erythropoietin was more effective in terms of pain level reduction and ROM improvement compared with dextrose and pulsed radiofrequency.